Deletion status of p16 in effusion smear preparation correlates with that of underlying malignant pleural mesothelioma tissue. Issue 11 (15th October 2015) - Hida, Tomoyuki; Matsumoto, Shinji; Hamasaki, Makoto; Kawahara, Kunimitsu; Tsujimura, Tohru; Hiroshima, Kenzo; Kamei, Toshiaki; Taguchi, Kenichi; Iwasaki, Akinori; Oda, Yoshinao; Honda, Hiroshi; Nabeshima, Kazuki
Abstract : Differentiating malignant pleural mesothelioma (MPM) cells morphologically from reactive mesothelial hyperplasia cells is problematic. Homozygous deletion (HD) of p16 ( CDKN2A ), detected by FISH, is a good marker of malignancy and is useful to differentiate between these cells. However, the correlation between the p16 status of effusion smears and that of the underlying MPM tissues has not been investigated. We used p16 ‐specific FISH to investigate 20 cases of MPM from which both effusion cytologic smears and histologic specimens were available. In five cases, histologic specimens included both an invasive component and surface mesothelial proliferation. In 14 cases (70%), MPM cells in both tissue sections and effusion smears were p16 HD‐positive. Conversely, MPM cells in the remaining six tumors (30%) were p16 HD‐negative in both tissue sections and effusion smears. For all five MPM cases with surface mesothelial proliferations and invasive components, the effusion smears, surface mesothelial proliferations, and invasive MPM components all displayed p16 deletion. Moreover, the extent to which p16 was deleted in smears highly correlated with the extent of p16 deletion in tissues. The p16 deletion percentages were also similar among smears, tissue surface proliferations, and invasive components. In cases with clinical and radiologic evidence of a diffuse pleural tumor, detection of p16 deletion in cytologic smear samples may permit MPM diagnosis without additional tissue examination. However, the absence of p16 deletion in cytologic smear samples does not preclude MPM. Abstract : This study demonstrated the correlation between the p16 deletion status of effusion cytology and that of underlying malignant pleural mesothelioma (MPM) tissues by fluorescence in situ hybridization (FISH) analysis for MPM cases in which both materials were available. To the best of our knowledge, this is the first study to evaluate the correlation of p16 FISH status in MPM between cytologic and histologic specimens. If p16 FISH status of cytologic preparations can predict that of the underlying MPM, it may be possible to diagnose MPM in cytologic preparations in cases with clinical and radiological evidence of a diffuse pleural tumor.